CONSOLIDATED FINANCIAL REPORTING AND AUDIT QUALITY IMPROVEMENT ISSUES - Avazov Ilkhom (Web of Journals Publishing, 2024)
In the process of presenting a consolidated financial report prepared in accordance with international standards, conclusions and recommendations are developed on the problems and their solutions that have arisen in the process of conducting an audit, improving the audit quality control system.
Keywords: audit process, financial reporting, consolidated financial reporting, external audit, international financial reporting standards, international auditing standards, joint-stock company, audit quality assessment.